The significant effect of floor surface roughness on slip resistance in public toilet in Tanah Merah, Kelantan / Muhammad Uzair Aiman Zainuddin, Salahuddin Abdul Hakeem Abas and Iryani Abdul Halim Choo - Zainuddin, Muhammad Uzair Aiman; Abas, Salahuddin Abdul Hakeem; Abdul Halim Choo, Iryani (2023)
Surface texture comprises surface roughness, which is frequently represented as roughness. Surface roughness influences by friction. It has been founded that surface roughness has a significant impact on the slip resistance between shoe heels and floor surfaces under various walking scenarios. The slipperiness of the public toilet floor is one of the risk variables that influences how frequently people slip and fall. Slip resistance is now regarded as a key characteristic of footwear. Continuous efforts are being made to decrease slip, trip, and fall accidents by increasing friction between shoes and floor contact. These problems persist because of the heavy traffic volume encountered during holidays. However, all public restrooms must be secure enough for users. Most of the previous study establishes friction measurement in relation to slipperiness evaluation of shoes and floor. Therefore, background increasing the traction of floor surfaces would be desired, but there not enough data to say whether traction properties are linearly connected with topographic features of the floor surfaces or what scales of surface roughness are necessary to successfully limit slipping hazards. This study builds on prior results about how public toilet floor surface finishes affect slip resistance performance for the best slip resistance controls in various surface roughness with varying type of floor. Depending on the type of floor being used to test slip resistance, the roughness of the surface will be measured. The evaluation of slipping hazard exposures that start the chain of events leading to an accident may be all that is needed to measure slipperiness. To prevent a loss of balance and an accident, it is necessary to consider human capacity to foresee slickness and adjust to risky settings. Expecting prediction to identify whether public toilet in Tanah Merah is safe to used or not.